Analysis of the albumin level, neutrophil-lymphocyte ratio, and platelet-lymphocyte ratio in Guillain-Barré syndrome - Ozdemir, Hasan Huseyin (Arquivos de Neuro-Psiquiatria, 2016)
The purpose of this study was to investigate the prognostic value of the pretreatment and post-treatment albumin level, neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR) in subtypes of Guillain-Barré syndrome (GBS). A retrospective analysis of 62 patients with GBS treated between 2011 and 2015 in Dicle University Hospital, Turkey, was carried out. The pretreatment and post-treatment albumin, NLR, and PLR were documented, together with acute inflammatory demyelinating polyradiculoneuropathy (AIDP), acute motor axonal neuropathy, motor sensory axonal neuropathy, and Hughes’ scores. Post-treatment albumin levels in GBS were significantly reduced, and albumin level was negatively correlated with the Hughes scores. Elevated pretreatment NLRs and PLRs were significantly associated with AIDP. There were no correlations between the Hughes scores, NLR, and PLR. The results point to a negative correlation between albumin levels and GBS disability and suggest that the NLR and PLR may be promising blood biomarkers of AIDP.
Keywords: Guillain-Barré syndrome; albumin; neutrophil-lymphocyte ratio; platelet-lymphocute ratio